Comparison of faecal indicator and viral pathogen light and dark disinfection mechanisms in wastewater treatment pond mesocosms. (15th May 2021) - Park, Jason B.K.; Weaver, Louise; Davies-Colley, Rob; Stott, Rebecca; Williamson, Wendy; Mackenzie, Margaret; McGill, Erin; Lin, Susan; Webber, Judith; Craggs, Rupert J.
Abstract: This study compared light and dark disinfection of faecal bacteria/viral indicator organisms ( E. coli and MS2 (fRNA) bacteriophage) and human viruses (Echovirus and Norovirus) in Wastewater Treatment Pond (WTP) mesocosms. Stirred pond mesocosms were operated in either outdoor sunlight-exposed or laboratory dark conditions in two experiments during the austral summer. To investigate wavelength-dependence of sunlight disinfection, three optical filters were used: (1) polyethylene film (light control: transmitting all solar UV and visible wavelengths), (2) acrylic (removing most UVB <315 nm), and (3) polycarbonate (removing both UVB and UVA <400 nm). To assess different dark disinfection processes WTP effluent was treated before spiking with target microbes, by ( a ) 0.22 μm filtration to remove all but colloidal particles, ( b ) 0.22 μm filtration followed by heat treatment to destroy enzymes, and ( c ) addition of Cytochalasin B to supress protozoan grazing. Microbiological stocks containing E. coli, MS2 phage, Echovirus, and Norovirus were spiked into each mesocosm 10 min before the experiments commenced. The light control exposed to all sunlight wavelengths achieved >5-log E. coli and MS2 phage removal (from 1.0 × 10 6 to <1 PFU/mL) within 3 h compared with up to 6 h in UV-filtered mesocosms. This result confirms that UVB contributes to inactivation of E. coli and viruses by direct sunlight inactivation. However, the very high attenuation with depth of UVB in WTP water (99% removal in the top 8 cm) suggests that UVB disinfection may be less important than other removal processes averaged over time and full-scale pond depth. Dark removal was appreciably slower than sunlight-mediated inactivation. The dark control typically achieved higher removal of E. coli and viruses than the 0.22 μm filtered (dark) mesocosms. This result suggests that adsorption of E. coli and viruses to WTP particles (e.g., algae and bacteria bio-flocs) is an important mechanism of dark disinfection, while bacteria and virus characteristics (e.g. surface charge) and environmental conditions can influence dark disinfection processes. Highlights: Removal of faecal/viral indicator organisms & human viruses were investigated. UVB contributes to inactivation of E. coli & viruses by direct sunlight inactivation. Dark removal was appreciably slower than sunlight-mediated inactivation. Adsorption of phage/viruses to WTP particles is a major mechanism for dark removal.